Calcium Isotopic Fractionation during Ion‐Exchange Column Chemistry and Thermal Ionisation Mass Spectrometry (TIMS) Determination. Issue 2 (28th November 2015) - Zhu, Hong L.; Zhang, Zhao F.; Wang, Gui Q.; Liu, Yu F.; Liu, Fang; Li, Xin; Sun, Wei D.
Abstract : Significant isotopic fractionation can occur during column chemistry and determination by mass spectrometry. Improper correction may produce uncertainties in the isotopic composition of geological samples. We investigated calcium isotopic fractionation during these two processes and set up a model to check data quality. The δ 44/40 Ca915a value of IAPSO seawater in different Ca cuts (e.g., 0–20, 20–40, 40–60, 60–80 and 80–100%) on column chemistry ranged from ~ 4‰ to 0‰. The more Ca was eluted, the lower the δ 44/40 Ca915a value of the elution was found. The isotopic fractionation of calcium on the column appeared to follow the exponential law. However, TIMS instrumental fractionation during Ca runs did not always follow the exponential law due to mixing effects from sample reservoirs on the filament. Our results show that errors could be caused if the instrumental fractionation deviates from the exponential law, especially when the fractionation degree is large. To improve the measurement uncertainty, a model is proposed to check the behaviour and degree of instrumental fractionation, which will provide a quick and reasonable verdict on the data quality of TIMS runs. Key Points: Significant calcium isotopic fractionation can occur during column chemistry and mass spectrometry measurements and generally follows the exponential law. The fractionation of Ca during TIMS runs may deviate from the exponential law and cause bias due to mixing reservoir effects. A model is proposed to eliminate outlying runs to improve measurement uncertainty.